Exploring digital remediation in support of personal reflection. Issue 110 (February 2018) - Thomas, Lisa; Briggs, Pam; Kerrigan, Finola; Hart, Andrew
Highlights: We explored the transformation of social media content into three radically different formats; a book, a triptych of photographs and film. Using interviews, we investigated users' responses to their remediated data. Our findings were used to develop a digital curation process to assist the development of different tools for social media analysis and display. Our paper establishes design implications to aid reflection on social media use through remediation. Abstract: Increasingly our digital traces are providing new opportunities for self-reflection. In particular, social media (SM) data can be used to support self-reflection, but to what extent is this affected by the form in which SM data is presented? Here, we present three studies where we work with individuals to transform or remediate their SM data into a physical book, a photographic triptych and a film. We describe the editorial decisions that take place as part of the remediation process and show how the transformations allow users to reflect on their digital identity in new ways. We discuss our findings in terms of the application of Goffman's (1959) self-presentation theories to the SM context, showing that a fluid rather than bounded interpretation of our social media spaces may be appropriate. We argue that remediation can contribute to the understanding of digital self and consider the design implications for new SM systems designed to support self-reflection.